The safety of ready-to-eat meals under different consumer handling conditions : a thesis presented in partial fulfilment of the requirements for the degree of Master in Food Technology at Massey University, Manawatū, New Zealand - Jiang, Fan (Massey University, 2016)
Microbial count is an important index to measure the safety status of a food. This trial aimed to determine the safety of eight meals (four meats and four vegetarians) by using the agar plate counting method to measure the populations of total bacteria and specific pathogenic microorganisms during four day’ abusing. The results showed that chicken & lemon sauce, pork & cranberry loaf and lasagne veg can be considered as acceptable after a series of handling steps including heating and holding in different environments. BBQ beef, quiche golden and pie rice & vegetable were all marginal for the microbial load before heating, but afterwards all of them were acceptable. Casserole chickpea and hot pot sausage were in marginal for the microbial load by the end of trial.
Keywords: Ready meals; Safety measures; Food handling; Consumer behaviour; Microbial count; Pathogenic microorganisms